Guarantee Of Clean Water Fulfillment For The Community In Kutai Kartanegara Regency Juridical Study In The Perspective Of Human Rights - Hengki Prima Hodding; Sudiarti Dewi Kurra (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
Water is the most important element presented by the creator in the midst of this world, the presence of water can help meet needs and create prosperity for the community, especially the availability of appropriate sanitation and clean water. However, in this case the state represented by the government to exercise power for the realization of people's welfare, sometimes has an apathetic attitude and action towards guaranteeing human rights, in the form of fulfilling the right to clean water for its people. This is especially felt by the people in Kutai Kartanegara district, East Kalimantan province, where local people receive water supply from the government that is not of poor quality because the water that flows to their homes is not clear but has a murky color and sometimes contains mud. Meanwhile, this research was carried out using a normative juridical research method, with a statutory and philosophical approach, through collecting primary and secondary legal sources, and then analyzing it using a qualitative descriptive method . The conclusion in this study is that the guarantee of human rights in the form of fulfilling clean water cannot be felt optimally and comprehensively by the people in Kutai Kartanegara district, East Kalimantan province, clean water is a human right that needs to be guaranteed by the state for community needs, both for household needs and industrial needs. and other needs that cannot be separated from clean water. Konstitusion of concerning health emphasizes that people have the right to enjoy clean and healthy water, in this case what is related to the author's research is that the water that flows in people's homes in Kutai Kartanegara district does not meet clean water standards. so that the community's rights in the aspect of clean water to meet their needs and guarantee their health are still being neglected by the state, in this case the government.